2019
DOI: 10.24326/asphc.2019.5.13
|View full text |Cite
|
Sign up to set email alerts
|

Ellagic Acid Content in Selected Wild Species of Fruit Roses

Abstract: Ellagic acid (EA) is a natural antioxidant, belonging to the group of polyphenolic compounds. It displays a broad spectrum of pro-health effects, ranging from the prevention of cancer to antiviral properties. It is present in many fruit from the rose family (Rosaceae): strawberries, raspberries, blackberries and walnuts as well as cranberries and grapes. The available literature states that the fruit of roses, in addition to their aesthetic and functional applications, also show therapeutic properties, which, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Average ± SD Average ± SD Average ± SD Average ± SD Average ± SD Average ± SD The rose achenes (FRU) were found to be a relatively rich source of phenolics representing different phenolic classes [1]. Karczmarz et al [21] showed the presence of free and bound PA in R. canina, R. moyesii, and R. pendulina achenes. Our previous study demonstrated the content of gallic, protocatechuic, caffeic, sinapic, p-coumaric, and ferulic acids in teas and tinctures from rugosa rose true fruits [1].…”
Section: Phenolic Acid Rt (Min) Lf-free Lf-ach Lf-alkh Fru-free Fru-amentioning
confidence: 99%
See 1 more Smart Citation
“…Average ± SD Average ± SD Average ± SD Average ± SD Average ± SD Average ± SD The rose achenes (FRU) were found to be a relatively rich source of phenolics representing different phenolic classes [1]. Karczmarz et al [21] showed the presence of free and bound PA in R. canina, R. moyesii, and R. pendulina achenes. Our previous study demonstrated the content of gallic, protocatechuic, caffeic, sinapic, p-coumaric, and ferulic acids in teas and tinctures from rugosa rose true fruits [1].…”
Section: Phenolic Acid Rt (Min) Lf-free Lf-ach Lf-alkh Fru-free Fru-amentioning
confidence: 99%
“…The large amounts of rose leaves and achenes constituting an interesting raw material for potential application are obtained from rose plantations every year. Although these rose organs are still being treated as plantation by-products and often discarded without any utilization, the interest in their potential use for commercial purposes (e.g., for preparation of nutraceuticals, functional foods, or pharmaceutical products) has continued to grow in recent years [14][15][16][17][18][19][20][21]. Moreover, rose leaves have been used in folk medicine to cure bronchitis and were found to exhibit anti-angiogenic, anti-inflammatory, and anti-nociceptive activities [22,23].…”
Section: Introductionmentioning
confidence: 99%